Equity and Relationship Maintenance in First Marriages and Remarriages. Issue 8 (17th November 2019) - Dainton, Marianne
ABSTRACT: Research indicates that individuals in remarriages experience less marital satisfaction than individuals in a first marriage. This study sought to determine whether variations in equity and maintenance might explain this phenomenon. A sample of 547 married individuals from the United States completed an online survey. Results suggested virtually no differences in the use of positive or negative maintenance by marriage type. Although maintenance use predicted a larger amount of the variance in satisfaction among those who were remarried, more maintenance behaviors entered the regression equation predicting satisfaction for individuals in first marriages. Finally, equity predicted the use of maintenance for both marriage types.